2003
DOI: 10.1093/jn/133.2.381
|View full text |Cite
|
Sign up to set email alerts
|

β-Carotene Regulates NF-κB DNA-Binding Activity by a Redox Mechanism in Human Leukemia and Colon Adenocarcinoma Cells

Abstract: We demonstrated previously that beta-carotene may affect cell growth by a redox mechanism. The purpose of this study was to determine whether the redox-sensitive transcription factor nuclear factor (NF)-kappaB may be involved in the growth-inhibitory and proapoptotic effects of the carotenoid. To test this hypothesis, human leukemic cells (HL-60) and colon adenocarcinoma cells (LS-174 and WiDr) were treated with beta-carotene, alone or in combination with alpha-tocopherol or N-acetylcysteine, and changes in 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(63 citation statements)
references
References 45 publications
1
58
0
4
Order By: Relevance
“…53 The same group of investigators reported earlier that ␤-carotene at doses responsible for growth-inhibitory effects in HT-29 cells, was able to regulate the redox regulation of NF-B and the subsequent expression of proteins, such as c-myc, involved in the induction of apoptosis. 54 However, it was discussed that the concentrations responsible for the prooxidant and the growth-inhibitory effects of ␤-carotene in this in vitro study would be reached in vivo in the serum of humans only with supplements containing very high doses of the carotenoids. 54 These in vitro studies clearly demonstrated that ␤-carotene and possibly other carotenoids inhibit colon cancer cells by their capability to induce apoptosis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…53 The same group of investigators reported earlier that ␤-carotene at doses responsible for growth-inhibitory effects in HT-29 cells, was able to regulate the redox regulation of NF-B and the subsequent expression of proteins, such as c-myc, involved in the induction of apoptosis. 54 However, it was discussed that the concentrations responsible for the prooxidant and the growth-inhibitory effects of ␤-carotene in this in vitro study would be reached in vivo in the serum of humans only with supplements containing very high doses of the carotenoids. 54 These in vitro studies clearly demonstrated that ␤-carotene and possibly other carotenoids inhibit colon cancer cells by their capability to induce apoptosis.…”
Section: Discussionmentioning
confidence: 90%
“…54 However, it was discussed that the concentrations responsible for the prooxidant and the growth-inhibitory effects of ␤-carotene in this in vitro study would be reached in vivo in the serum of humans only with supplements containing very high doses of the carotenoids. 54 These in vitro studies clearly demonstrated that ␤-carotene and possibly other carotenoids inhibit colon cancer cells by their capability to induce apoptosis.…”
Section: Discussionmentioning
confidence: 90%
“…Blocking the NF-ĸB pathway stops cell proliferation, induces apoptosis and makes the cancer cell more susceptible to antitumor agents. Preliminary studies have demonstrated that β-carotene as well has the ability to modulate NF-ĸB signaling pathway by means of a redox mechanism to tumor cells (Palozza et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…31,32) The anti-oxidative/anti-inflammatory effects of thiol molecules (glutathione and N-acetyl-L-cysteine), and dietary polyphenols (quercetin and resveratol) have all been shown to play a role in controlling NF-kB activation with subsequent effects on inflammatory gene expression. 33,34) Our recent study reported that betaine suppressed the redox-sensitive transcription factor, NF-kB, in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%